Book review: Hiba Bou Akar, For the War Yet to Come: Planning Beirut's Frontiers. (May 2019) - Simon, AbdouMaliq
Hiba Bou Akar, For the War Yet to Come: Planning Beirut's Frontiers . Standford, California: Stanford University Press, 2018, 264pp., $28.00. ISBN: 1503605604, 9781503605602.